Le Grand Paris et l’axe Seine - Brennetot Arnaud; Michel Bussi; Yves Guermond (Métropoles)
This article presents the metropolitan project « Axe Seine », which emerged in the context of the reflections about « Greater Paris ». We analyse the process of cooperation initiated since 2008 and the discourses exchanged in public between the actors concerned by the project. The case of the « Axe Seine » offers an interesting opportunity to account for the geoethical frames of reference mobilized by the actors to think the development of the Parisian metropolis extended to the Seine valley. Analytically studying the justifications put forward by the actors of the project enables us to underline the fact that competition represents the main motivation expressed by those in charge of the spatial planning of the « Axe Seine », which brings to light the weight of neoliberal governmentality in the metropolitan public debate. Looking back on the origins of neoliberalism allows us to understand how the implementation of the neoliberal ideology on the international scale went hand in hand with a naturalization, on the local scale, of the principles that legitimate it.